Elevated Functional Connectivity in a Striatal-Amygdala Circuit in Pathological Gamblers - Peters, Jan (Public Library of Science, 2013)
Both substance-based addiction and behavioural impulse control disorders (ICDs) have been associated with dysfunctions of the ventral striatum. Recent studies using functional connectivity techniques have revealed increased coupling of the ventral striatum with other limbic regions such as amygdala and orbitofrontal cortex in patients with substance abuse disorders and attention-deficit hyperactivity disorder. In the present study, we re-analyzed previously published functional magnetic resonance imaging data acquired in pathological gamblers and controls during value-based decision-making to investigate whether PG is associated with similar functional connectivity effects. In line with previous studies in other ICDs, we observed reliable increases in functional coupling between striatum and bilateral amygdala in gamblers vs. controls. Implications of these findings for neural models of self-control and addiction are discussed.